The “Belt and Road” Initiative and Overseas Chinese in Southeast Asia - Akira Yonemoto (Borong Newinera Publisher, 2020)
Since China's proposal of the “Belt and Road” initiative in 2013, the relationship between China and Southeast Asia has continued to develop. This achievement is inseparable from a large number of overseas Chinese living in Southeast Asia. As an indispensable and unique force to promote the construction of the “Belt and Road”, the Southeast Asians Chinese have played an irreplaceable role: such as support of Chinese culture spreading, building confidence and disambiguation among countries, and economic and trade cooperation. The problems and challenges facing Chinese culture in Southeast Asia are not only related to the development of Chinese society in Southeast Asia but also the current development of Chinese native culture. To overcome the problems and challenges encountered in the process of inheriting Chinese culture in Southeast Asia, we must clearly understand the status of overseas Chinese and the role that overseas Chinese can play to maximize their role and influence as carriers and bridges.